Correction: An investigation on the influence of catalyst composition, calcination and reduction temperatures on Ni/MgO catalyst for dry reforming of methane. Issue 56 (14th September 2020) - Rashid, Muhammad Usman; Wan Daud, W. M. A.
Abstract : Correction for 'An investigation on the influence of catalyst composition, calcination and reduction temperatures on Ni/MgO catalyst for dry reforming of methane' by Muhammad Usman Rashid et al., RSC Adv., 2016, 6, 91603–91616, DOI: ; 10.1039/C6RA15256B .